2023
DOI: 10.1186/s12959-023-00482-7
|View full text |Cite
|
Sign up to set email alerts
|

The risk for post-thrombotic syndrome of subjects with deep vein thrombosis in an Indonesian referral hospital: a retrospective cohort study

Abstract: Background Post-thrombotic syndrome (PTS) is a complication of deep vein thrombosis (DVT) and affects 20–40% of DVT subjects. The risk factor of PTS after DVT is difficult to determine. We aimed to evaluate the incidence of PTS after 3 months of DVT diagnosis and to determine the risk of PTS. Methods A retrospective cohort study of subjects who developed DVT confirmed by Doppler ultrasound in Cipto Mangunkusumo Hospital from April 2014 until June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Collectively, serum expression of lncRNA NORAD gene had considerable diagnostic and prognostic significance in discriminating DVT patients and healthy people. In addition, our present results also indicated the close relationship of age and D-dimer with the development of PTS, which was consistent with the previous evidence [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, serum expression of lncRNA NORAD gene had considerable diagnostic and prognostic significance in discriminating DVT patients and healthy people. In addition, our present results also indicated the close relationship of age and D-dimer with the development of PTS, which was consistent with the previous evidence [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The period of publication is mainly from 2016 to 2023. The countries of publication included China ( 9 , 11 , 12 , 18 , 21 ), Norway ( 10 , 28 ), Canada ( 13 ), the Netherlands ( 14 , 16 , 25 ), Japan ( 15 ), Indonesia ( 17 ), Australia ( 19 ), Switzerland ( 20 ), Israel ( 22 , 23 ), Pakistan ( 24 ) and Poland ( 26 , 27 ). For the background of morbidity, only one of the studies ( 10 ) reported a background of pregnancy-related venous thrombosis, while the remaining 19 had a background of deep vein thrombosis (DVT).…”
Section: Resultsmentioning
confidence: 99%